2020
DOI: 10.1037/adb0000586
|View full text |Cite
|
Sign up to set email alerts
|

More behavioral recommendations produce more change: A meta-analysis of efficacy of multibehavior recommendations to reduce nonmedical substance use.

Abstract: Death and morbidity associated with substance use have risen continuously over the last few decades, increasing the need for rigorous examination of promising programs. Interventions attempting to change multiple behaviors have been designed to address interconnected problems such as use of both alcohol and drugs. This meta-analysis aimed to examine the efficacy of multibehavior interventions to curb nonmedical substance use in relation to the theoretical relation among different substance use behaviors. Speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 118 publications
0
2
0
Order By: Relevance
“…As shown, although the number of observations is smaller as the number of recommendations exceeds four, no clear pattern of a curvilinear relation appeared in our data. This finding of a linear effect of the number of recommendations on behavioral and clinical outcomes is consistent with those of prior meta-analyses of HIV (Sunderrajan et al, 2021) and substance-use (Dai et al, 2020) interventions, although one meta-analysis from the lifestyle domain suggested an inverted-U relationship (see Wilson et al, 2015). Regarding the causes of such mixed findings, despite the inclusion of different domains and study reports, the differences may be due to different analytic methods.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…As shown, although the number of observations is smaller as the number of recommendations exceeds four, no clear pattern of a curvilinear relation appeared in our data. This finding of a linear effect of the number of recommendations on behavioral and clinical outcomes is consistent with those of prior meta-analyses of HIV (Sunderrajan et al, 2021) and substance-use (Dai et al, 2020) interventions, although one meta-analysis from the lifestyle domain suggested an inverted-U relationship (see Wilson et al, 2015). Regarding the causes of such mixed findings, despite the inclusion of different domains and study reports, the differences may be due to different analytic methods.…”
Section: Discussionsupporting
confidence: 86%
“…Most of these covariates were suggested by previous meta-analyses synthesizing domain-specific evidence (cf. Dai et al, 2020; Sunderrajan et al, 2021; Wilson et al, 2015) and, if they predicted effect sizes, were included in the CHE+ models that tested how the number of behavioral recommendations affected behavioral and clinical change.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the same methods as other recent publications that have used other components of this project (Dai et al, 2020; Sunderrajan et al, 2021), which spanned various domains. We searched MEDLINE, APA PsycInfo, and EBSCO through July 27, 2022.…”
Section: Methodsmentioning
confidence: 99%
“…We also specified the single-behavior intervention as the reference group. The effect sizes represent changes in outcomes from the pretest to the posttest, which is the optimal approach when clinical trials use a variety of control groups (Dai et al, 2020; Sunderrajan et al, 2021). A review of the literature showed only one meta-analysis about multiple-behavior interventions (Sunderrajan et al, 2021).…”
Section: Health Disparities and Multiple Risksmentioning
confidence: 99%